(untitled) (Research, Society and Development, 2022)
The aim of this study was to characterize the solid residue of bamboo shoot processing, which corresponds to more than 70% of the raw material, beyond the technological properties and cyanide removing. Pre-processing was carried out in boiling water for 30, 45, 60, and 90 minutes. Control, treated and pre-treated residue samples were dried in an oven with air circulation for 48 hours at 65 ± 5 °C followed by milling in knife mill and standardized in particle size 60 mesh sieve. The powder showed low lipids content and high fiber, protein and mineral contents proportional to the traditional flours. The technological properties were evaluated for water and oil retention capacity, showing high values, that was proved by analysis of scanning electron microscopy (SEM), which showed high porosity structure. Regarding the presence of cyanogenic glycosides, it was concluded that pre-processing and drying significantly reduced but not eliminated taxiphyllin, which generates an alert to the processing of this material as safe foods, however demonstrating to be an important absorbent material in the treatment of oil-contaminated waters and soils.